STUDY OF THE STATE OF ENT-ORGANS IN CHILDREN WITH ANOMALIES AND DEFORMATIONS OF DENTOALVEOLAR APPARATUS AND SPEECH DISORDERS - P.S. Flis; N.V. Raschenko; A.O. Melnyk; V.V. Filonenko; O.I. Kotov (Український стоматологічний альманах)
The relevance of research. When examining patients with dentoalveolar anomalies, children with speech disorders can often be observed. For orthodontists, it is important to diagnose the etiologic component of these disorders, namely, whether they are the cause of diseases of the ENT-organs and whether they are directly related to orthodontic pathology. In order to study the impact of the pathology of the ENT-organs on the formation of speech disorders, clinical and additional examination methods were carried out. In case of respiratory tract narrowing due to the deviated septum, hypertrophic or allergic rhinitis, adenoid vegetations, hypertrophy of the tonsils, speech pathology may be observed. Specified pathologies are subject to treatment before the logopedic and orthodontic correction. According to our clinical study in children of the main group and of the comparison group, the apparent pathology of the nose and oropharynx was not detected. Subjective and objective methods of hearing examination also did not reveal deviations from the norm. For a more detailed study of the condition of the upper respiratory tract, it is advisable to use computer tomography of the skull and magnetic resonance therapy of the head.